Assume that for each observation $i = 1,\ldots, N$, we have $M$ equations:
$$
y_{i,j} = x_{i,j}\beta_j + \varepsilon_{i,j}
$$
Where $i = 1,\ldots, N$ enumerates individuals and and $j = 1,\ldots, M$ enumerates the equations. here $x$ is of size $1 \times k_j$ and $\beta_j$ is of size $k_j \times 1$ and $k_j$ is the number of covariates for regression $j$. Stacking over all $i = 1,\ldots N$, we get $M$ equations:
$$
y_j = X_j \beta_j + \varepsilon_j
$$
where now $X_j$ is of size $N \times k_j$. For simplicity, assume that $X_j$ are non-stochastic. Next, assume that for all $i = 1,\ldots, N$ and $j = 1,\ldots, M$:
$$
\begin{align*}
&\mathbb{E}(\varepsilon_{i,j}) = 0,\\
&\mathbb{E}(\varepsilon_{i,j}^2) = \sigma_{jj}
\end{align*}
$$
For the covariance between equations, let for all $i = 1,\ldots, N$ and $j,\ell = 1,\ldots, M$:
$$
\mathbb{E}(\varepsilon_{i,j} \varepsilon_{i,\ell}) = \sigma_{j,\ell}
$$
while for all $j,\ell = 1,\ldots, M$ and $i,i' = 1,\ldots, N$ with $i \ne i'$:
$$
\mathbb{E}(\varepsilon_{i,j}, \varepsilon_{i',k}) = 0
$$
This means that errors for the same individual might be correlated across equations, while errors for different individuals are uncorrelated.
This can be expressed more compactly as:
$$
cov(\varepsilon_j, \varepsilon_{\ell}) = \sigma_{j,\ell}I_N
$$
Now, let us stack the various equations, one on top of the other:
$$
y = Z\beta + \varepsilon,
$$
where:
$$
y = \begin{bmatrix} y_1\\y_2\\ \vdots\\y_M\end{bmatrix},
\varepsilon = \begin{bmatrix} \varepsilon_1 \\ \vdots \\ \varepsilon_M \end{bmatrix},\\
Z = \begin{bmatrix} X_1 & 0 & \ldots & 0\\
0 & X_2 & \ldots & 0,\\
\vdots & \vdots & \ddots & \vdots\\
0 & 0 & \ldots & X_M
\end{bmatrix}, \beta = \begin{bmatrix} \beta_1\\ \vdots \\ \beta_M\end{bmatrix}
$$
The variance-covariance matrix of $\varepsilon$ takes the form:
$$
\mathbb{E}(\varepsilon \varepsilon') = V = \begin{bmatrix} \sigma_{11} I_N & \sigma_{12}I_N & \ldots & \sigma_{1M} I_N\\
\sigma_{21} I_N & \sigma_{22} I_N & \ldots & \sigma_{2N} I_N\\
\ldots & \ldots & \ddots & \vdots\\
\sigma_{M1} I_N & \ldots & \ldots & \sigma_{MM}I_N
\end{bmatrix} = \Sigma \otimes I_N
$$
where $\otimes$ is the Kronecker product and:
$$
\Sigma = \begin{bmatrix}\sigma_{11} & \sigma_{12} & \ldots & \sigma_{1M}\\
\sigma_{21} & \sigma_{22} & \ldots & \sigma_{2M}\\
\vdots & \vdots & \ddots & \vdots\\
\sigma_{M1} & \sigma_{M2} & \ldots & \sigma_{MM}
\end{bmatrix}
$$
$\Sigma$ gives the variance covariance matrix of the errors for a fixed individual.
For the Kronecker product, we have the rules: $(A \otimes B)^{-1} = A^{-1} \otimes B^{-1}$ and $(A \otimes B)(C \otimes D) = AC \otimes BD$ and $(A \otimes B)' = A' \otimes B'$ .
Let $\hat \Sigma$ be the estimate of $\Sigma$ based on an initial OLS estimation of $y_j$ on $X_j$ and let $\hat V = \hat \Sigma \otimes I_N$. Then the feasible GLS estimator is given by:
$$
\begin{align*}
\hat \beta &= (Z' \hat V^{-1} Z)^{-1} Z' \hat V^{-1} y,\\
&=(Z'(\hat \Sigma \otimes I_N)^{-1}Z)^{-1}Z'(\hat \Sigma \otimes I_N)^{-1}y,\\
&= (Z'(\hat \Sigma^{-1}\otimes I_N)Z)^{-1}Z'(\hat \Sigma^{-1}\otimes I_N)y,\\
&= \beta + (Z'(\hat \Sigma^{-1}\otimes I_n)Z)^{-1}Z'y
\end{align*}
$$
Now, let us assume that all the $X_i$ are identical, say $X$, then $Z = I_M \otimes X$ and we can further simplify:
$$
\begin{align*}
\hat \beta &= (Z'(\hat \Sigma^{-1}\otimes I_N)Z)^{-1}Z'(\hat \Sigma^{-1}\otimes I_N)y,\\
&= ((I_M \otimes X)'(\hat \Sigma^{-1}\otimes I_N)(I_M \otimes X))^{-1}(I_M \otimes X)'(\hat \Sigma^{-1}\otimes I_N)y,\\
&= ((I_M \hat \Sigma^{-1}\otimes X'I_N)(I_M \otimes X))^{-1}(I_M \hat \Sigma^{-1} \otimes X' I_N)y,\\
&= (\hat \Sigma^{-1} \otimes X'X)^{-1}(\hat \Sigma^{-1}\otimes X')y,\\
&= (\hat \Sigma \otimes (X'X)^{-1})(\hat \Sigma^{-1}\otimes X')y,\\
&= (\hat \Sigma\hat \Sigma^{-1} \otimes (X'X)^{-1}X')y\\
&= (I_M \otimes (X'X)^{-1} X')y
\end{align*}
$$
Notice that $\hat \Sigma$ disappeared from this equation. The last one equation can be written in the following way:
$$
\hat \beta = \begin{bmatrix} (X'X)^{-1}X'y_1\\
(X'X)^{-1} X'y_2\\
\vdots\\
(X'X)^{-1}X' y_1
\end{bmatrix} = \beta + \begin{bmatrix}(X'X)^{-1}X'\varepsilon_1,\\ (X'X)^{-1}X'\varepsilon_2\\\vdots \\ (X'X)^{-1}X'\varepsilon_M\end{bmatrix}
$$
So the feasible GLS estimates are identical to the OLS estimates from an equation by equation estimation. Notice that this also means that the residuals $\hat \varepsilon_j$ will be identical to the residuals from an OLS estimation.
Now to estimate the variance covariance matrix, we take the product $(\hat \beta - \beta)(\hat \beta - \beta)'$ which gives a matrix with entries:
$$
\begin{align*}
(\hat \beta_{j} - \beta_j)(\hat \beta_j - \beta_j)' &= [(X'X)^{-1}X' \varepsilon_j][(X'X)^{-1}X'\varepsilon_j]',\\
&= (X'X)^{-1}X'\varepsilon_j \varepsilon_j'X(X'X)^{-1}
\end{align*}
$$
Then for equation $j$, we have the variance covariance matix:
$$
V(\hat \beta_j) = \mathbb{E}((\hat \beta_j - \beta_j)(\hat \beta_j - \beta_j)) = \sigma_{jj}\left(X'X\right)^{-1},
$$
As $\sigma_{jj}$ is not known, it is usually estimated by $\hat \sigma_{jj} = \frac{1}{N}\sum_i \hat \varepsilon_{i,j}^2$ where $\hat \varepsilon_{i,j}$ are the residuals of the feasible GLS estimator. However, in this case, these will be identical to the residuals of an OLS estimator (as the estimators $\hat \beta$ are identical). As such, the estimates of the variances of $\hat \beta$ for the SUR will be identical to the variance estimates of the OLS estimates (equation by equation).